Cytomegalovirus Hepatitis During Pregnancy - Ying Chan; Maria Kean-Chong; David Gonzalez; Joseph Apuzzio (Hindawi Limited, 1995)
Background: Although cytomegalovirus (CMV) is an uncommon cause of viral hepatitis during pregnancy, a definitive diagnosis is important because of the potential for congenital CMV. In the case reported here, a diagnosis of hepatitis caused by CMV was made after the more common viral pathogens had been ruled out.